Proceedings of the International Seminar on Public Health and Education 2018 (ISPHE 2018) 2018
DOI: 10.2991/isphe-18.2018.57
|View full text |Cite
|
Sign up to set email alerts
|

Building Cooperation Interpersonal Skill in Physical Education Lessons Through Traditional Game

Abstract: Cooperation as interpersonal skill is one of the four important competencies that must be possessed by learners to be able to lead a successful life in the 21st century. Therefore, teachers, who are usually only concerned with assisting students to meet certain hard-skill qualifications, are now also required to include cooperation in their objective. Therefore, teachers, including physical education teachers, must be able to develop teaching materials to meet such demands and all the while promoting physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…It is evident that games may represent an important factor for triggering the health benefits of PE [36]. Therefore, for all that is stated above, the aim of this study was to assess the effect of a game-based physical fitness program on health-related physical fitness and psychological health variables in schoolchildren from primary education.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that games may represent an important factor for triggering the health benefits of PE [36]. Therefore, for all that is stated above, the aim of this study was to assess the effect of a game-based physical fitness program on health-related physical fitness and psychological health variables in schoolchildren from primary education.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the lack of physical activity, it was concluded that the physical fitness of the children was poor (Weston et al, 2019). Physical education lesson; an increase in the percentage of MVPA is observed when it is carried out in outdoor games based on a physical activity away from monotony and when it is carried out with activities that require team play and cooperationoriented activities (Hartatiti et al, 2018;Wang and Zhou, 2022). When the physical education course is conducted by these criteria, students obtain MVPA degrees greater than 50% in swimming (Cardon et al, 2004), football (Harvey et al, 2016), basketball (Iserbyt et al, 2022), and handball units (Dania et al, 2017).…”
Section: Physical Activitymentioning
confidence: 99%
“…This finding was confirmed by Ceballos Gurrola et al [37], who conducted a ball game program with elementary school children, in which it obtained a significant improvement in the metabolic profile of students in the experimental group compared to those in the control group. Based on the facts above, it is clear that the game is one of the important factors in physical education material to improve physical fitness related to health [38]. Therefore, this study aimed to validate the game material to improve physical fitness related to the health of children with special needs in elementary school.…”
Section: Introductionmentioning
confidence: 99%